2018
DOI: 10.11609/jott.4311.10.11.12443-12450
|View full text |Cite
|
Sign up to set email alerts
|

The terrestrial life of sea kraits: insights from a long-term study on two Laticauda species (Reptilia: Squamata: Elapidae) in the Andaman Islands, India

Abstract: Sea kraits forage in water and return to land to digest their prey, mate, slough, and lay their eggs.  The temporal terrestrial patterns in encounter rate and behaviour of two species of sea kraits Laticauda colubrina and L. laticaudata were studied over four years at the New Wandoor beach in the southern Andaman Islands.  The encounter rate of L. colubrina was found to be 20 times higher than L. laticaudata, and sea kraits were observed to prefer the natural refuge that the microhabitat of uprooted trees prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Sea kraits slough at more frequent intervals compared to terrestrial snakes (Shankar & Whitaker, 2009 ; Shetty & Shine, 2002a ) to remove attached marine organisms that would induce drag, meaning that finding suitable habitats for this behavior is likely to be important. Sea kraits have been shown to consequently use trees and other objects, such as rocks, as sloughing areas (Brischoux & Bonnet, 2009 ; Tyabji, Mohanty, Young & Khan, 2018 ). In our study, all of the sloughing locations were in the crevices of trees created by thick bark or decaying parts of the trunk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sea kraits slough at more frequent intervals compared to terrestrial snakes (Shankar & Whitaker, 2009 ; Shetty & Shine, 2002a ) to remove attached marine organisms that would induce drag, meaning that finding suitable habitats for this behavior is likely to be important. Sea kraits have been shown to consequently use trees and other objects, such as rocks, as sloughing areas (Brischoux & Bonnet, 2009 ; Tyabji, Mohanty, Young & Khan, 2018 ). In our study, all of the sloughing locations were in the crevices of trees created by thick bark or decaying parts of the trunk.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations assist in marine locomotion but hinder movement on land (Brischoux, Kato, Ropert‐Coudert & Shine, 2010 ; Wang, Lillywhite & Tu, 2013 ). More terrestrial members of the genus Laticuada may travel further inland compared to more aquatic species (Brischoux & Bonnet, 2009 ; Tyabji et al, 2018 ), as they are better adapted to energy efficient movement on land. Therefore, sea kraits may be avoiding travel further than necessary to reach locations with conditions suitable for digesting prey, thereby reducing their energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea kraits are highly philopatric and considered to be seasonal breeders (Shetty 2000;Shetty and Shine 2002). Bhaskar (1996) and Tyabji et al (2018) observed courting groups of Yellowlipped Sea Kraits during the months of November and December in the South Reef and New Wandoor regions of the Andaman Islands, respectively, while Shetty and Shine (2002) observed frequent courting in the months of October and November in Fijian populations and Brischoux and Bonnet (2009) observed courting of Laticauda saintgironsi during November and December in New Caledonia. Our record of a courting group in September shows that breeding might commence earlier than has been previously recorded in Andaman populations.…”
Section: O N S E R V At I O N a N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…
I ndia is home to two species of sea kraits, the Blue-lipped Sea Krait (Laticauda laticaudata) and the Yellow-lipped Sea Krait (Laticauda colubrina), both of which are found along the coasts of the Andaman and Nicobar Archipelago (Bhaskar 1996;Whitaker and Captain 2004;Rangasamy et al 2018;Tyabji et al 2018) and in a few instances along the coasts of Calcutta (Smith 1943). The ecology of these species in India is known from a few studies in the Andaman Islands
…”
mentioning
confidence: 99%